Simulation of a stepless-speed variable reluctance torque coupler / Khairul Anwar Abd Hamid - Abd Hamid, Khairul Anwar (2007)
This thesis consist a study of reluctance torque coupler (RTC). The objective is to modify the switch reluctance motor (SRM) model to represent the RTC. A 2 phase 4/6 pole SRM with voltage rating 12V is used for the modification. The SRM block diagram was given by the supervisor and the simulation will be done using MATLAB Simulink program.